Forensic toxicology mechanisms and pathology - Powers, Robert H.; Dean, Dorothy E. (CRC Press, Taylor & Francis Group, 2016)
The book provides an understanding of the mechanistic basis of the action of drugs and toxins, addressing their physiologic and pathologic consequences on the affected organ system.